Role of soil moisture versus recent climate change for the 2010 heat wave in western Russia. Issue 6 (19th March 2016) - Hauser, Mathias; Orth, René; Seneviratne, Sonia I.
Abstract: The severe 2010 heat wave in western Russia was found to be influenced by anthropogenic climate change. Additionally, soil moisture‐temperature feedbacks were deemed important for the buildup of the exceptionally high temperatures. We quantify the relative role of both factors by applying the probabilistic event attribution framework and analyze ensemble simulations to distinguish the effect of climate change and the 2010 soil moisture conditions for annual maximum temperatures. The dry 2010 soil moisture alone has increased the risk of a severe heat wave in western Russia sixfold, while climate change from 1960 to 2000 has approximately tripled it. The combined effect of climate change and 2010 soil moisture yields a 13 times higher heat wave risk. We conclude that internal climate variability causing the dry 2010 soil moisture conditions formed a necessary basis for the extreme heat wave. Key Points: Soil moisture conditions of 2010 led to a sixfold heat wave risk increase in western Russia Recent climate change has approximately tripled the heat wave risk The soil moisture anomaly in 2010 would have been large even without anthropogenic climate change